2022
DOI: 10.1016/j.msard.2022.103524
|View full text |Cite
|
Sign up to set email alerts
|

Fingolimod impairs inactivated vaccine (CoronaVac)-induced antibody response to SARS-CoV-2 spike protein in persons with multiple sclerosis

Abstract: Background : The impact of disease-modifying treatments on humoral response induced by inactivated severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines is understudied. Methods : We recruited 34 persons with multiple sclerosis (MS) under fingolimod treatment and 25 healthy individuals. Anti-SARS-CoV-2 spike IgG indices were measured by ELISA in sera of participants after CoronaVac vaccinations. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“… 23 Therefore, although accumulating evidence and our results confirmed that S1PRM therapy blunted responses to SARS-CoV-2 vaccination, the impact of this treatment on COVID-19 outcomes in pwMS remains to be elucidated. Moreover, several studies identified a negative correlation between humoral response after COVID-19 vaccination and treatment duration of S1PRMs, 46 , 47 which deserves further verification.…”
Section: Discussionmentioning
confidence: 84%
“… 23 Therefore, although accumulating evidence and our results confirmed that S1PRM therapy blunted responses to SARS-CoV-2 vaccination, the impact of this treatment on COVID-19 outcomes in pwMS remains to be elucidated. Moreover, several studies identified a negative correlation between humoral response after COVID-19 vaccination and treatment duration of S1PRMs, 46 , 47 which deserves further verification.…”
Section: Discussionmentioning
confidence: 84%
“…High-certainty evidence confirms significantly lower odds of post-vaccination seroconversion in pwMS on S1PRM compared with UX people (OR [95%CI]: 0.04 [0.03, 0.06], P<0.00001) (Supplementary Figure 5). All included studies 16,17,19-22,25-31 found significantly lower concentrations of antibodies following vaccination in these pwMS compared to UX people. Studies with heterogenous effect measures (moderate-certainty evidence) indicate that with the current vaccination strategy, pwMS on S1PRM are 25 times (95%CI: 16.66, 33.33) less likely to show anti-S1, and 8.33 times (95%CI: 3.70, 20) less likely to show anti-S seroconversion following COVID-19 vaccination (Chi 2 =7.24, P<0.01).…”
Section: Resultsmentioning
confidence: 93%
“…All included studies 16,17,[19][20][21][22][25][26][27][28][29][30][31] , headto-head mRNA-AV 29 and mRNA-inactivated 22 immunogenicity comparisons in S1PRM-treated pwMS have suggested the opposite. Hence, the need for more replication of inactivated/mRNA/AV comparisons is clearly sensed for pwMS on S1PRM.…”
Section: Sphingosine-1-phosphate Receptor Modulators (S1prm)mentioning
confidence: 99%
“…S1PRM extensively decrease the odds of post-vaccine seroconversion (OR (95% CI): 0.04 (0.03 to 0.06), p<0.00001) (online supplemental figure 5), according to evidence with high certainty. In all of the included studies,10 11 13–16 19–25 the S1PRM-treated pwMS had significantly lower concentrations of post-vaccine antibodies when compared with UX people; the effect measures were, however, heterogenous. Therefore, evidence indicates with moderate certainty that pwMS on S1PRM are 25 times (95% CI: 16.66 to 33.33) less likely to show anti-S1, and 8.33 times (95% CI: 3.70 to 20) less likely to show anti-S seroconversion following COVID-19 vaccination (χ 2 =7.24, p<0.01).…”
Section: Resultsmentioning
confidence: 97%